2022
DOI: 10.1021/acssuschemeng.2c02881
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Pyrolysis of Waste Polyethylene Using Combined CaO and Ga/ZSM-5 Catalysts for High Value-Added Aromatics Production

Abstract: Amidst the global focus on recycling and treatment of waste plastics for resource sustainability, it is a huge challenge to convert waste plastics into aromatics, especially high value-added monocyclic aromatic hydrocarbons (MAHs). In this work, catalytic pyrolysis experiments of linear low-density polyethylene (LLDPE) indicated that the selectivity to aromatics increased from 70.35% when using pure HZSM-5 to 94.02% with 7 wt % Ga-modified HZMS-5. Further, the cracking catalyst CaO was utilized to increase the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Some relevant works have reported that the LAS of zeolite could be enhanced by a dopant of heteroatoms. The reaction showed remarkable selectivity to aromatics, which will be fully discussed in section 4.1.…”
Section: The Structure–activity Relationships In Catalytic Cracking O...mentioning
confidence: 94%
“…Some relevant works have reported that the LAS of zeolite could be enhanced by a dopant of heteroatoms. The reaction showed remarkable selectivity to aromatics, which will be fully discussed in section 4.1.…”
Section: The Structure–activity Relationships In Catalytic Cracking O...mentioning
confidence: 94%
“…Moreover, the inorganic additives present in some samples might have some synergistic effects during catalytic pyrolysis that led to different product distribution than in the case of VPP. More recently, Fu et al [17] described the synergistic effect of CaO when using HZSM-5based catalysts for the pyrolysis of polyethylene.…”
Section: Influence Of Feedstockmentioning
confidence: 99%
“…In this context, zeolites are interesting catalytic materials due to their remarkable properties, e.g., acidity and porosity, which Amer Inayat can be exploited in cracking, olefination as well as aromatization during thermocatalytic pyrolysis of plastics. Recently, there has been a growing interest in using zeolite-based catalysts for the thermocatalytic pyrolysis of plastics in general and polyolefin plastics in particular and several reports in open literature on this topic can be found [6,10,12,[14][15][16][17][18]. However, studies showing the influence of different types of waste polyolefins in conjunction with different reactor configuration/ operation mode are rather scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Polystyrene (PS) is often used in packaging, appliances, automotive, and insulation, which undergoes slow natural environmental degradation. , The incineration of PS produces heat, while toxic polycyclic aromatic hydrocarbons are inevitably generated . Pioneering oxidation methods have been developed to decompose PS into carbon dioxide that can efficiently decrease the plastic residue in the environment. , Catalytic pyrolysis is another common method to convert waste plastics into small molecules, aromatics, and aviation oil. Besides, the upgrading of PS to value-added chemicals will motivate the sorting and recovery of plastic. …”
Section: Introductionmentioning
confidence: 99%